Fondements et approche d’un modèle cognitif du déplacement - Pierre-Emmanuel Michon; David Duguay; Geoffrey Edwards (Cybergeo, 2007)
The CADMUS system produces maps of real and perceived difficulties of displacements in complex buildings, for valid people or for those suffering of a physical or perceptive disability. Using a numerical model of the environment as a foundation and a descriptive model of the user, CADMUS generates maps of the accessible spaces as perceived by the user. The maps thus produced allows building administrators and therapists to evaluate accessibility of the buildings for people taking into account their physical and cognitive state, along with the modifications of perception associated with these.